2019
DOI: 10.1530/eje-18-0254
|View full text |Cite
|
Sign up to set email alerts
|

MRI T2 signal intensity and tumor response in patients with GH-secreting pituitary macroadenoma: PRIMARYS post hoc analysis

Abstract: Objective Pituitary adenoma MRI T2 signal intensity associates with tumor characteristics including responsiveness to somatostatin analogs (SSAs). These analyses determined whether baseline T2 signal intensity predicts response to primary medical treatment with long-acting SSA. Design Post hoc analyses of the prospective multicenter, open-label, single-arm PRIMARYS study in which patients with treatment-naïve GH-secreting pituitary macroadenomas received fixed-dose lanreotide autogel (120 mg) every 4 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 15 publications
4
17
2
1
Order By: Relevance
“…Also, the analysis evaluated only some of the possible predictive factors for response to acromegaly treatment; there are others, such as tumor histopathology (as discussed in the "Introduction") or expression of somatostatin receptors that may also contribute to how patients respond. A recent post hoc analysis of the PRIMARYS data found that IGF-1 levels after treatment with lanreotide autogel were lower in patients with T2-signal hypointense GH-secreting macroadenomas compared with T2-signal isointense GH-secreting macroadenomas, hence assessment of T2-signal intensity was suggested as a predictive factor for long-term response [30]. It should also be noted that the decision to treat with SRLs may not only depend on predictive factors, but also on the cost of medication and availability of experienced surgeons; both of these factors may vary considerably between countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the analysis evaluated only some of the possible predictive factors for response to acromegaly treatment; there are others, such as tumor histopathology (as discussed in the "Introduction") or expression of somatostatin receptors that may also contribute to how patients respond. A recent post hoc analysis of the PRIMARYS data found that IGF-1 levels after treatment with lanreotide autogel were lower in patients with T2-signal hypointense GH-secreting macroadenomas compared with T2-signal isointense GH-secreting macroadenomas, hence assessment of T2-signal intensity was suggested as a predictive factor for long-term response [30]. It should also be noted that the decision to treat with SRLs may not only depend on predictive factors, but also on the cost of medication and availability of experienced surgeons; both of these factors may vary considerably between countries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that several factors may influence the response to SRLs. These include: age and sex; pre-treatment and early post-treatment TV, GH, and IGF-1 levels; tumor histopathology (Ki-67, somatostatin receptor subtype 2 expression, AIP expression, granularity, β-arrestin expression); imaging characteristics (T2-weighted magnetic resonance imaging signal intensity); genetic factors; and treatment history [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Older age, female sex, and lower IGF-I levels at baseline were associated with increased probability of achieving long-term biochemical control, but tumor volume response at 12 weeks was not an accurate predictor of subsequent tumor volume control [ 59 ]. Further, patients with a hypointense tumor on T2 MRI showed greater reductions in IGF-I and were more likely to achieve tumor shrinkage [ 60 ]. These results suggest that patient- and tumor-specific factors at baseline may predict long-term biochemical response to primary SRL treatment, while early tumor response may not.…”
Section: Injectable Srlmentioning
confidence: 99%
“…T2-weighted MRI signal of the adenoma has been recently recognized as a non-invasive predictor of response to first-generation SRL therapy in acromegaly. Somatotroph adenomas with lower T2-signal intensity are frequently smaller and less invasive than adenomas with a higher T2-signal intensity (9,10,11,12), but the correlation with first-generation SRL-induced tumor shrinkage was inconsistent among studies (9,11,13,14). Although T2-hypointense adenomas are associated with higher GH levels at diagnosis (10), these patients have greater GH and IGF-1 reductions after a median of 6 months of presurgical first-generation SRLs treatment than patients with T2-iso-or T2-hyper-intense adenomas (9,11,14).…”
Section: Introductionmentioning
confidence: 99%